PENGARUH LINGKUNGAN KERJA FISIK,LINGKUNGAN KERJA NONFISIK DAN STRES KERJA TERHADAP KINERJA KARYAWAN (Studi pada PT. Kereta Api Indonesia (PERSERO) Daerah Operasional IV Semarang) - Widianingrum, Ayu; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2016)
This study is aim to analize the influence of physical work environment, non physical work environment, stress on performance on employee performance in PT. Kereta Api Indonesia (Persero) Daerah Operasional IV Semarang. This study is applied toward 64 employees in PT. Kereta Api Indonesia (Persero) Daerah Operasional IV Semarang. Sampling techniques in this study using purposive sampling method. The data analysis method used in this study include validity, reliability, classic assumption test, multiple linear regression analysis, F test, t test, and the coefficient of determination. The result of this study indicates: 1) physical work environment has does not significantly impact to the employee performance, 2) non physical environment has positive and significant impact to the employee performance, 3) stress on performance has not significantly impact to the employee performance.